2019
DOI: 10.26905/jkdp.v23i1.2405
|View full text |Cite
|
Sign up to set email alerts
|

Internal factors and firm value: A case study of banking listed companies

Abstract: The weakening of the value of the rupiah against the US dollar has made Indonesia again experiencing economic crisis conditions. However, this condition did not make the performance of the banking sector share decline and vice versa, defeating nine other industrial sectors, this indicates that the firm value in the banking sector is still considered good by investors, which are the factors that influence the firm value? This study aims to analyze the factors that influence firm value in the banking sector and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The debt to equity ratio (DER) is the debt ratios that is predicted to affect FV. The higher the DER, the Subing & Susiani (2019) which found that DER has a negative effect on FV meaning that an increase in debt will be followed by a decrease in the FV.…”
Section: The Effect Of Debt To Equity Ratio On Firm Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The debt to equity ratio (DER) is the debt ratios that is predicted to affect FV. The higher the DER, the Subing & Susiani (2019) which found that DER has a negative effect on FV meaning that an increase in debt will be followed by a decrease in the FV.…”
Section: The Effect Of Debt To Equity Ratio On Firm Valuesmentioning
confidence: 99%
“…The company's ability to obtain shareholders benefits is important in measuring FV, it can be seen through EPS. Companies must be able to influence share prices in the capital market in order to increase FV by increasing the value of traded stock (Subing & Susiani, 2019). Kholis, Sumarmawati, & Mutmainah (2018); Kusuma & Priantinah (2012) explained that EPS has an effect on FV, the higher the EPS, the higher the FV.…”
Section: Introductionmentioning
confidence: 99%
“…Namun hasil berbeda ditemukan oleh Ida (2010) menunjukkan bahwa 5 dari 7 perusahaan memilih pendanaan hutang daripada ekuitas modal internal. Perbedaan hasil juga ditemukan oleh Subing et al (2019) bahwa faktor internal tidak berpengaruh pada nilai perusahaan sektor bank. Adanya perbedaan pendapat hasil penelitian dahulu dapat memperkuat penelitian ini menguji empiris teori pecking order yang memilih sumber dana internal lebih disukai manajemen perusahaan untuk peningkatan nilai perusahaan.…”
Section: Sri Hermuningsihunclassified
“…The company's capital structure can come from within the company, in the form of capital owner ownership and retained earnings, or outside the company, in the form of loans or debt. Determining the optimal capital structure target proportion between foreign capital, debt, and own capital is the main task of company management (Subing & Susiani, 2019). Foreign investors are increasingly investing their money in Indonesian companies due to the increasing opportunities for Indonesia's economic growth rate and support from free trade.…”
Section: Introductionmentioning
confidence: 99%